Chiral separation of (d)- and (l)-enantiomers of doxylamine succinate in rat plasma - Tadiboyina Sirisha; Bannimath Gurupadayya; Bharathkumar Inturi (Faculty of Pharmacy, Cairo University, 2015)
A selective chiral ultra fast liquid chromatography (UFLC-DAD) method was developed and validated to separate and quantify the (d)- and (l)-enantiomers of doxylamine in rat plasma. After extraction of the plasma samples with acetonitrile, the separation of doxylamine succinate enantiomers and internal standard (I.S., diphenhydramine hydrochloride) was achieved on a cellulose Tris (4-chloro,3-methylphenylcarbamate) column with a mobile phase of 20 mM ammonium bicarbonate buffer-acetonitrile (65:35 v/v) with 0.15% diethylamine in the buffer at a flow rate of 1.0 mL/min. The diode array (DAD) detection wavelength was set at 220 nm. The peaks obtained were identified as (d) and (l) by injecting the pure (d) form into the liquid chromatography and comparing the chromatograms. The effect of column oven temperature on the retention of doxylamine and mobile phase variables which have an effect on the enantiomers separation like ionic strength, type and concentration of organic modifier was studied. Linear calibration curves were obtained over the range of 100-1400 ng/mL in plasma for both enantiomers (R2 > 0.995). The mean extraction recoveries were 94.5-104.7% of rat plasma. The mean relative standard deviation (RSD%) of accuracy and intra-day and inter-day precision for both enantiomers were ⩽10%. The method can be further applied to determine the pharmacokinetics of (d)- and (l)-enantiomers in rat plasma.